Metabolic stress conditions dictate MAPKAPK2-dependent efficiency of MEK1/2 inhibition in colorectal carcinoma - Niti Kumari; Xu Chen; Amber M. Baldwin; Kristin I. Clemons; Mohammad El-Harakeh; Lilian E. Calisto; Balawant Kumar; Qiaoqiao Zhang; Jiang Min; Bin Xiao; Amar B. Singh; Bin Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
The kinase MAPKAPK2 regulates cell survival, proliferation, and death, and is upregulated in colorectal carcinoma (CRC) where it is associated with tumor growth and progression. However, how it regulates tumor progression in conjunction with other signaling pathways, such as MEK/ERK, remains elusive. Solid tumors are often subjected to metabolic stress, notably glucose deprivation. Here, we demonstrate that MAPKAPK2 protein levels in CRC regulate cell fate decision during stress conditions, such as glucose deprivation and therapeutic treatment. While MAPKAPK2 expression is a limiting factor for CRC growth in vitro, depleting MAPKAPK2 or inhibiting its activity pharmacologically provides a survival advantage to CRC cells under glucose limiting conditions. Subjecting CRC cells to low glucose resulted in an ERK1/2-mediated decline in MAPKAPK2 to promote survival. Additionally, cells with reduced MAPKAPK2 activity were less sensitive to trametinib under glucose limiting conditions. Utilizing transcriptomic profiling, we found that glucose deprivation and MAPKAPK2 depletion activate pathways associated with survival during metabolic stress. This relationship was also observed in CRC patients (TCGA), where tumors with low MAPKAPK2 expression had higher ERK1/2 activation and upregulated stress-induced pathways, leading to poor survival. Finally, MAPKAPK2 modulated growth of CRC organoids, subcutaneous tumors, and patient-derived xenografts (PDX), and reduced MAPKAPK2 levels decreased efficacy of trametinib, in vitro and in vivo. Overall, this study identifies an interrelationship between MEK/ERK and p38/MAPKAPK2 signaling pathways during glucose deprivation to support cell survival and features MAPKAPK2 loss as a possible mechanism leading to reduced efficacy of trametinib-based anticancer therapy and poor patient outcomes in CRC.